Disability and motorcycle taxi drivers in Cartagena, Colombia - Yaneth Herazo B; Regina Domínguez A; Sandra Olarte B; Liliseth Quitian C (Universidad de Antioquia, 2011)
Objective: to estimate the functional dependency as a measure of disability in a group of motorcycle taxi drivers from Cartagena, Colombia. Methods: a retrospective descriptive study in which researchers reviewed 1123 files of motorcycle taxi drivers involved in traffic accidents in Cartagena during 2006. The level of functional dependence regarding performance of some basic activities of daily life was determined for 262 subjects using the Barthel scale. Furthermore, data analysis was carried out using the EpiInfo 3.5.1 database, and variables are presented in absolute and relative frequencies. Results: it was found that 53.4% of subjects had mild functional dependence and 15.6% had moderate dependence. 76% of the participants said they were unemployed. Conclusions: functional dependence as a measure of disability is a highly probable result of traffic accidents among motorcycle taxi drivers.